Stereoselective Total Synthesis of Cryptomoscatone F1 - Srinivas, Eedubilli; Dutta, Palash; Ganganna, Bogonda; Alghamdi, Ahmad Alkhazim; Yadav, Jhillu Singh (Synthesis, 2016)
A concise stereoselective total synthesis of cryptomoscatone F1 has been accomplished by utilization of asymmetric acetate aldol reaction, Brown’s asymmetric allylation, and olefin cross-metathesis as key transformations.
Keywords: cryptomoscatone F1; acetate aldol reaction; Brown’s asymmetric allylation; olefin cross-metathesis